Circulating thyroid hormones and metabolites in children with autism spectrum disorder - Hancock, Michael; Zhang, Rui; Brown, Suzanne J.; Boyder, Conchita; Mullin, Shelby; Campbell, Purdey J.; Wilson, Scott G.; Lim, Ee Mun; Whitehouse, Andrew J.O.; Walsh, John P. (Frontiers in Endocrinology, 2026)
ContextThyroid hormones affect neurological development and function, but detailed studies of thyroid hormones and metabolites in autism are lacking.ObjectiveTo characterize thyroid function and metabolism in autistic children.MethodologyThis cross-sectional study compared 788 autistic children (mean age 7.6 ± 3.9 years, 78% male) with 301 non-autistic children (mean age 7.8 ± 4.0 years, 48% male; comprising 215 (71.4%) non-autistic siblings of participants and 86 (28.6%) unrelated individuals). Plasma TSH, free T4 (FT4) and free T3 (FT3) were measured by automated immunoassay, and total T4, total T3 and thyroid hormone metabolites by customized liquid chromatography-tandem mass spectrometry (LCMS/MS). Regression analyses were adjusted for age and sex.ResultsTSH concentrations were similar in autistic and non-autistic children (median 2.3 vs 2.1 mU/L, P = 0.64). FT4 was significantly lower in autistic children (18.4 vs 18.7 pmol/L, P = 0.0003), as was FT3 (7.0 vs 7.1pmol/L, P<0.0001), with no significant difference in the FT4:FT3 ratio (P = 0.24). Total T4 was lower in autistic children (178 vs 194 nmol/L, P = 0.0026, as was total T3 (2.2 vs 2.4 nmol/L, P = 0.018), with no significant difference in the T4:T3 ratio (P = 0.099). Two metabolites were significantly lower in autistic children: 3,5-T2 (0.010 vs 0.021 nmol/L, P<0.0001) and 3,3’-T2 (0.12 vs 0.16 nmol/L, P<0.0001), whereas T0 levels were higher (1.5 vs 1.1 nmol/L, P = 0.028).ConclusionsCirculating thyroid hormones and metabolites differ between autistic and non-autistic children, although the observed differences are small. The study demonstrates the utility of LCMS/MS for in-depth characterization of thyroid hormone economy, with potentially wide applications.